Bio-Inspired Radio-Frequency Source Localization Based on Cochlear Cross-Correlograms - Wang, Yingying; Mandal, Soumyajit (Frontiers in Neuroscience, 2021)
This paper describes a bio-inspired radio frequency (RF) scene analysis system based on cross-correlating the outputs of two single-chip RF spectrum analyzers. The latter are implemented using digitally-programmable “RF cochlea” chips (in 65 nm CMOS) that integrate a transmission-line active cochlear model, consisting of 50 parallel exponentially-spaced stages for analyzing the radio spectrum from 1.0-8.3 GHz, together with an output encoding network. The encoders convert the analog outputs of all cochlear stages into parallel delta-sigma (∆-Σ) modulated digital signals for real-time demodulation and analysis by a digital back-end processor. These outputs can also be multiplied with each other to generate cochlear correlation matrices (known as cross-correlograms). Simulation results demonstrate the use of cross-correlograms for wide-range time-delay estimation and real-time multi-source localization at different frequencies and input signal-to-noise (SNR) ratios. Over-the-air measurement results from an experimental two-channel RF scene analysis prototype confirm the use of such time-delay estimates, which are analogous to interaural time differences (ITDs) in the auditory system, for azimuthal source localization at 3.4 GHz. In addition, differences in received signal strength at the two cochleas, which are analogous to interaural level differences (ILD) in biology, are also used to localize RF sources.